PENGGUNAAN KOMIK SEBAGAI MEDIA PEMBELAJARAN TERHADAP UPAYA MENINGKATKAN MINATMATEMATIKA SISWA SEKOLAH DASAR (SD/MI) - NEGARA, HASAN SASTRA (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2014)
The condition of Mathematics, whose image is a non-enjoyable subject for students, must be taken into endless reflection by all concerned parties, especially for teachers whose responsibility is to deliver the learning material to the students. Tedious learning material presentation should be anticipated by providing means of material presentation which are innovative, fun, and able to draw students’ interest.One of the alternatives in providing innovative material presentation is by using comic as a media. Considering the tendency students posse in having interest toward comic, it can be argued that comic is usable as learning media. By inserting mathematics concepts into comics or explaining learning material in form of comics, it is expected that students’ emotional factor and interest are drawn into activities in effort to learn the material. In addition, comic being a visual media is assumed as able to give influence toward the acqusition of knowledge because it can draw students’ attention and interest when the information is delivered. Comic is also one of the alternatives in choosing fun and interractive learning media. The writer argues that the use of comic as media can motivate students to learn, so that the negative image of mathematics that students have in their mind as dificult and non-enjoyable subject can be replaced by mathematics as an enjoyable subject which will draw students attention and interest. In result, students achievement in learning mathematics is expected to improve. Moreover, the use of comic as a media can be combined with various learning models as an additional touch in delivering learning material and it can be twisted by inserting small games in the learning process. As a teacher, we are expected to embed good character values into the comics character we make and use.